Architectural fragments dispersed next to the Entrance Gateway - Temples of India Project Team (Jio Institute, 2024)
Different architectural fragments are dispersed next to the pratoli (entrance gateway), in the premises of the Mahanaleshwar temple complex. Seen here are fragments of a pillar capital, part of the samvarna shikhara (pyramidical superstructure) of the mandapa (pillared hall), and a pillar fragment. Minute carvings on the round shaft remnant of the pillar.